2010
DOI: 10.1007/s00064-010-8026-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Large Acetabular Defects Using Trabecular Metal Augments

Abstract: Between 2005 and 2007, 38 patients with acetabular defects type IIIa und IIIb according to Paprosky underwent reconstruction using the TMT system (Trabecular Metal Technology). After 25 months, a significant functional improvement was seen in all patients. The Merle d'Aubigné Score increased from 6 points preoperatively to 13 points postoperatively, the Harris Hip Score from 29 to 78 points. Two revisions were necessary because of loosening or migration of the cup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Grappiolo et al 4 reported a Harris Hip Score of 40 preoperatively, vs. 90.5 postoperatively. Hasart et al 34 assessed only patients with Paprosky 3A and 3B defects, using the evaluation criteria of Merle D’Aubigne and Postel, 8 and reported an improvement from 6 to 13 points in the postoperative period. Similar increments to those found in the literature were observed in the present patients, with a preoperative mean of 6.67 vs. 4.83 in the postoperative period; the best parameter was improvement of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Grappiolo et al 4 reported a Harris Hip Score of 40 preoperatively, vs. 90.5 postoperatively. Hasart et al 34 assessed only patients with Paprosky 3A and 3B defects, using the evaluation criteria of Merle D’Aubigne and Postel, 8 and reported an improvement from 6 to 13 points in the postoperative period. Similar increments to those found in the literature were observed in the present patients, with a preoperative mean of 6.67 vs. 4.83 in the postoperative period; the best parameter was improvement of pain.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean correction was 17 mm. Hasart et al 26 reported that there was an improvement in the center of rotation of the hip from 35 mm (range: 16–55 mm) to 14 mm (range: 5–27). Siegmeth et al 27 reported that there was an improvement in the center of rotation from 50 mm to 28 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Borland et al 25 reported a wedge incorporation rate of 100% among 24 cases over a five-year period. Among 38 patients with type IIIA and IIIB defects who were followed up for 25 months, Hasart et al 26 reported that two cases required revision due to loosening or migration. In 34 patients with defects ranging from type IIA to type IIIB who were followed up for 24 months, Siegmeth et al 27 reported survival of 94.11%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, porous titanium and its alloys are commonly used for clinical applications under loading conditions because one can adjust their porosity and mechanical features in order to mimic the bone properties for each site of implantation. This enables its use for orthopedic applications, such as fixation screws, spinal fixation devices, artificial ligament anchors, dental implants, and foot and ankle reconstructive wedges [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%